Buying vs. Renting a Home in View of Young Adults in Poland - Marek Bryx (MDPI AG, 2021)
The deteriorating housing situation of young adults in many countries has become a subject of global interest. Researchers point to a number of factors that influence young adults’ decisions to own or rent a home. This paper examines the relationship between young adults’ inclination to own their own home and a range of different socio-economic factors. The study is of a quantitative-qualitative nature and was based on the results of a computer-assisted web interview (CAWI) questionnaire. The survey was conducted among young Poles aged 18–45 (n = 983). To analyse the results of the questionnaires, a logistic regression was used in which 24 different dichotomous and categorical variables were considered. Taking into account a number of individual characteristics (e.g., gender, education, hometown population size, etc.), the results show, for example, that single individuals and those with a higher level of tolerance for mortgage interest rates are more likely to own a home than to rent. This result highlights the desirability of easier access to mortgage credit. At the other end of the spectrum are those living with parents and those with dependents. The results imply that they are less interested in buying a home. Interestingly, declarations of a lack of funds for an own contribution when buying a new house/dwelling, or reluctance to expose oneself to financial difficulties throughout one’s life, do not discourage young adults from striving for their own dwelling, which further demonstrates the need to create appropriate mechanisms/instruments to facilitate the purchase of a dwelling for young adults.